Comparative study of manganese oxides with different oxidation states for catalytic carbonylation of n-butylamine by CO2. (February 2023) - Sun, Dalei; Peng, Liang; Cheng, Kang; Zheng, Yuying; Jiang, San Ping
Abstract: The four manganese oxides with different oxidation states (MnO, MnO2, Mn2 O3, Mn3 O4 ) was synthesized using the hydrothermal method through adjusting process parameters and feedstock ratio, and their catalytic performances for the carbonylation of n-butylamine by CO2 were also investigated. The results showed that the catalytic activities of manganese oxides with different oxidation states in the catalytic carbonylation of n-butylamine by CO2 follow the order of MnO2 > Mn3 O4 > Mn2 O3 > MnO, in which MnO2 with the Mn 4+ ion exhibited as high as 91.60% yield of N, N'-dibutylurea using polyethylene glycol 400 (PEG 400) as solvent under the reaction conditions of 160 ℃, 4 h, and 5.0 MPa. And then a series of characterization including XRD, XPS, H2 -TPR, and CO2 /NH3 -TPD were performed on the as-synthesized manganese oxides with different oxidation states, indicating that the content of oxygen vacancy on the surface of the manganese oxides with different oxidation states plays a key role in catalytic performances of the carbonylation of n-butylamine with CO2 . Graphical Abstract: ga1 Highlights: N, N′-dibutylurea was synthesized by carbonylation of 1-butanamine by CO2 over the manganese catalysts. The four manganese oxides with different oxidation states (MnO, MnO2, Mn2 O3, Mn3 O4 ) were synthesized by hydrothermal method. The MnO2 with the Mn 4+ ion exhibited highly active, non-toxic, and easily recycled. Its high activity is attributed to high concentration of surface oxygen vacancy.